1994
DOI: 10.1002/ar.1092380402
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies and immunolocalization of enamel proteins in rodent secretory stage ameloblasts processed by various cryofixation methods

Abstract: These results indicate that, despite some limitations, it is possible to adequately cryofix tooth organs while preserving the architecture of ameloblasts and permitting immunolocalization of enamel proteins. Furthermore, they confirm the general morphology of secretory stage ameloblasts as currently derived from conventional chemical tissue processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Proteins which play a role in the nucleation of calcium phosphates in enamel and dentine include amelogenin and collagen I, respectively. Collagen I, from dentine, was observed to penetrate across the DEJ into enamel (Lin et al, 1993) and amelogenins were also found in the mantle dentine (Nanci et al, 1994). As the specimens in the present investigation were prepared from mature permanent teeth, it would be logical to infer that the crystals observed at the DEJ are reflective of both enamel and dentine since the relevant proteins from both tissues are present at the DEJ during the developmental stage.…”
Section: Microstructural Features At the Dejmentioning
confidence: 79%
“…Proteins which play a role in the nucleation of calcium phosphates in enamel and dentine include amelogenin and collagen I, respectively. Collagen I, from dentine, was observed to penetrate across the DEJ into enamel (Lin et al, 1993) and amelogenins were also found in the mantle dentine (Nanci et al, 1994). As the specimens in the present investigation were prepared from mature permanent teeth, it would be logical to infer that the crystals observed at the DEJ are reflective of both enamel and dentine since the relevant proteins from both tissues are present at the DEJ during the developmental stage.…”
Section: Microstructural Features At the Dejmentioning
confidence: 79%
“…Such preorganization can result from different mechanisms. It is well documented that amelogenins are secreted by ameloblasts and are present during DEJ mineralization in both tissues (Nanci et al 1994). The mineralization of the outer dentin layer could induce an immobilization of amelogenins.…”
Section: Discussionmentioning
confidence: 99%
“…These two characteristics were also considered as their only common property for a long time. Recent cellular biology data on the extracellular matrix (ECM) components and their expression in odontoblast and ameloblast cells showed complex relationships between both tissues (Nanci et al 1994). The development of individual enamel and dentin crystals appeared, however, to be roughly comparable and was described in a four-step process (Houllé et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Samples fixed with 1% glutaraldehyde or with the aldehyde mixture were post-fixed with potassiumferrocyanide-reduced osmium tetroxide (Neiss, 1984), dehydrated in acetone, and routinely processed for embedding in Epon. Some segments of glutaraldehyde-fixed material were cryoprotected with 30% glycerol and dehydrated by freeze-substitution in 1% osmium tetroxide in pure acetone, as previously described (Nanci et al, 1994). Ultrathin sections of tissues were stained with uranyl acetate and lead citrate and examined with a Philips 400 or a JEOL JEM 2000FX-II electron microscope operated at 80 kV.…”
Section: Morphological Characterization Of Enamel Growth Sitesmentioning
confidence: 99%